2020
DOI: 10.1007/s11356-020-10965-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of divided convective-dispersive transport model to simulate variability of conservative transport processes inside a planted horizontal subsurface flow constructed wetland

Abstract: This paper offers a novel application of our model worked out in Maple environment to help understand the very complex transport processes in horizontal subsurface flow constructed wetland with coarse gravel (HSFCW-C). We made tracer measurements: Inside a constructed wetland, we had 9 sample points, and samples were taken from each point at two depths. Our model is a divided convective-dispersive transport (D-CDT) model which makes a fitted response curve from the sum of two separate CDT curves showing the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…As a result, the enormous onsite space needed to promote CWs in metropolitan areas is severely constrained. While it may seem at first glance that centralized WTSs need less onsite acreage than CWs, Fan et al (2021) found that widespread deployment of WTSs in municipalities may cause a significantly more amount of land usage in upstream operations, which might put further strain on the accessible land resources.…”
Section: Impact Implications From Treatment Purposes and Scenario Ana...mentioning
confidence: 99%
“…As a result, the enormous onsite space needed to promote CWs in metropolitan areas is severely constrained. While it may seem at first glance that centralized WTSs need less onsite acreage than CWs, Fan et al (2021) found that widespread deployment of WTSs in municipalities may cause a significantly more amount of land usage in upstream operations, which might put further strain on the accessible land resources.…”
Section: Impact Implications From Treatment Purposes and Scenario Ana...mentioning
confidence: 99%
“…Constructed wetlands (CWs) are made up of shallow lagoons or channels (depths of less than 1 m) that are planted with local species that are typical of humid areas, in which the decontamination processes take place through interactions between the water, solid substrates, microorganisms, vegetation, and even fauna [24]. Based on the water circulation characteristics, constructed wetlands can be classified into surface and subsurface flows [25]. In contrast to surface flow wetlands, their subsurface equivalents admit higher organic loads, reduce the risk of contact with the population, and prevent the appearance of insects [26].…”
Section: Introductionmentioning
confidence: 99%